Solubility Enhancement of a Poorly Water-Soluble Drug Using Hydrotropy and Mixed Hydrotropy-Based Solid Dispersion Techniques - Hezha Abdullah Ali; Hunar Kamal Omer (Advances in Pharmacological and Pharmaceutical Sciences)
Purpose. The biopharmaceutics classification system places rosuvastatin calcium in class II has a low and fluctuating oral bioavailability. The research focus is to maximize rosuvastatin calcium solubility in water and dissolution rate by employing and combining various hydrotropic agents to make a solid dispersion using solvent evaporation techniques. Methodology. The experimental study was conducted at Duhok University, College of Pharmacy. Initially, assess rosuvastatin’s solubility in hydrotropic agents including urea, mannitol, citric acid, sodium benzoate, and sodium salicylate at concentrations of 10, 20, 30, and 40% w/v. Then, various ratios of 2 and 3 hydrotropic agents were employed to reduce the concentration of each hydrotropic agent. By using a solvent evaporation procedure, solid dispersions were made. The solid dispersion powders underwent evaluation for their percentage drug content, percentage yield, solubility, dissolution test, XRD, DSC, SEM, and FTIR. For statistical analysis, GraphPad InStat Demo software was used to conduct a two-way analysis of variance (ANOVA). Results. In comparison to the pure drug, the solubility of hydrotropic solid dispersions and physical mixtures of rosuvastatin with a combination of hydrotropic agents (sodium salicylate, sodium benzoate, and urea) in the ratio of 13.33 for each increased in all formulations significantly, and all manufactured formulations’ drug release ranged from 98.83 to 104.78%, indicating a noticeably higher dissolution rate. Conclusion. The concept of mixed hydrotropic solid dispersion was shown to be an original, risk-free, and cost-effective method for enhancing the bioavailability of drugs that have a low degree of solubility in water.